ANALISIS TERHADAP PENOLAKAN PERDAMAIAN PADA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) OLEH KREDITUR SEPARATIS DALAM PERKARA KEPAILITAN - Ginting, Vida Rianita; Fitriani, Riska; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Suspension of Debt Payment is a certain period of time that is given to borrowers who can not pay off debts that have on due time or matured and can be billed, to submit a plan and negotiate to creditors. The peace in negotiation in PKPU ever happened to PT Maja Supreme Latexindo (PT MAL) proposed by one of the unsecured creditors namely Erwito. PT.MAL has a debt owed to unsecured creditors and creditors separatist, but one of the separatist creditors, namely PT. BRI, Putri Hijau Medan branch did not agree with the peace agreed upon by the other creditors by reason that the peace in violation of Article 285 Verse 2 part a, b, and c, 2 of Verse 281 of Law No. 37 of 2004 concerning with Bankruptcy and PKPU ( UUK and PKPU ).The objectives of this paper were, firstly to determine the application process of PKPU request by Erwito and peace proposed by PT . PT MAL against unsecured creditors. Secondly, to determine and analyze the reasons for the PT.BRI to reject peace proposed by PT . MAL. Thirdly, to know peace settlement efforts on PKPU between PT . BRI Putri Hijau Medan Br\qanch and PT . MAL . This type of research was normative juridical research.The conclusions drawn in this study were firstly, the application submitted by Erwito was in conformity with the requirement of the request PKPU namely Article 222 Verse 1 and 3 of UUK and PKPU and peace proposed by PT . MAL was in conformity with Article 281 UUK and PKPU. Secondly, the reason of PT BRI to reject peace agreed upon by debtor and other creditors referring to Article 285 , verse 2 a, b and c were not proven. Thirdly, the legal effort to do by PT BRI was to declare the debtor bankrupt if PT. MAL can not implement the agreement contents as stipulated in Article 255 Verse 1 of the UUK and PKPU and can apply for bankruptcy if it fulfills Article 2 Verse 1 of the UUK and PKPU. PT. BRI can also take legal actions to file an application in a civil case if the debt PT . MAL to PT BRI Putri Hijau Medan branch have not been paid.The suggestions to pose by the author is as follows. Firstly, for business doers, especially before applying for a declaration of bankruptcy should have enough knowledge about PKPU . Secondly , the judges verdict should explain the reason that the proposal is contrary to UUHT and peace achieved because of the conspiracy. Thirdly, bankruptcy regulation should provide an explanation of Article 285 , verse 2 , part b and c . Fourthly ,UUK and PKPU should first set before bankruptcy. Fifthly, the parties involved should do a peace treaty rights.Key words : PKPU- Peace – Legal Efforts